Cross-sectional and longitudinal associations of acrolein exposure with pulmonary function alteration: Assessing the potential roles of oxidative DNA damage, inflammation, and pulmonary epithelium injury in a general adult population. (September 2022) - Wang, Bin; Yu, Linling; Liu, Wei; Yang, Meng; Fan, Lieyang; Zhou, Min; Ma, Jixuan; Wang, Xing; Nie, Xiuque; Cheng, Man; Qiu, Weihong; Ye, Zi; et al.
Graphical abstract: Highlights: Urinary acrolein metabolites (UAMs) were repeatedly measured over a period of 3 years. UAMs were cross-sectionally associated with pulmonary function (PF) reduction. UAMs were longitudinally associated with PF decline in 3 years. 8-OHdG, CRP, and CC16 aggravated and/or mediated acrolein-associated PF reduction. This is the first study to report the associations of UAMs with PF. Abstract: Background: Acrolein is a significant high priority hazardous air pollutant with pulmonary toxicity and the leading cause of most noncancer adverse respiratory effects among air toxics that draws great attention. Whether and how acrolein exposure impacts pulmonary function remain inconclusive. Objectives: To assess the association of acrolein exposure with pulmonary function and the underlying roles of oxidative DNA damage, inflammation, and pulmonary epithelium integrity. Methods: Among 3, 279 Chinese adults from the Wuhan-Zhuhai cohort, associations of urinary acrolein metabolites (N-Acetyl-S-(2-carboxyethyl)-L-cysteine, CEMA; N-Acetyl-S-(3-hydroxypropyl)-L-cysteine, 3HPMA) as credible biomarkers of acrolein exposure with pulmonary function were analyzed by linear mixed models. Joint effects of biomarkers of oxidative DNA damage (8-hydroxy-deoxyguanosine), inflammation (C-reactive protein, CRP), and pulmonary epithelium integrity (Club cell secretory protein, CC16) with acrolein metabolites on pulmonary function and the mediating roles of these biomarkers were assessed. Besides, a subgroup (N = 138) was randomly recruited from the cohort to assess the stabilities of acrolein metabolites and their longitudinal associations with pulmonary function change in three years. Results: Significant inverse dose–response relationships between acrolein metabolites and pulmonary function were found. Each 10-fold increment in CEMA, 3HPMA, or ΣUACLM (CEMA + 3HPMA) was cross-sectionally related to a 68.56-, 40.98-, or 46.02-ml reduction in FVC and a 61.54-, 43.10-, or 50.14-ml reduction in FEV1, respectively ( P < 0.05). Furthermore, acrolein metabolites with fair to excellent stabilities were found to be longitudinally associated with pulmonary function decline in three years. Joint effects of acrolein metabolites with 8-hydroxy-deoxyguanosine, CRP, and CC16 on pulmonary function were identified. CRP significantly mediated 5.97% and 5.51% of CEMA-associated FVC and FEV1 reductions, respectively. 8-hydroxy-deoxyguanosine significantly mediated 6.78%, 6.88%, and 7.61% of CEMA-, 3HPMA-, and ΣUACLM-associated FVC reductions, respectively. Conclusions: Acrolein exposure of general adults was cross-sectionally and longitudinally related to pulmonary function decline, which was aggravated and/or partly mediated by oxidative DNA damage, inflammation, and pulmonary epithelium injury.